Food estate vs. smart farming: Rice production strategies for national food security - Risya Putri Pertiwi (Journal of Agrosociology and Sustainability, 2026)
Background: Indonesia’s food security faces complex pressures due to climate change, environmental degradation, and a high dependence on rice as the staple food. The government has responded to these challenges through the food estate program, which is based on large-scale land extensification. Various studies indicate that this program has low productivity, high ecological risks, and is unable to make a significant contribution to long-term food security. On the other hand, smart farming, which has been successfully implemented in countries such as Japan, Malaysia, and Brazil, demonstrates that technology-based precision intensification has significant potential to improve production efficiency without land expansion. Methods: The method used is a qualitative descriptive-comparative approach through the analysis of academic literature, policy documents, national statistical data, and international studies related to smart farming. Findings: The results show that productive food estate cultivation land accounts for less than 5% of the target and only produces 5.1–5.2 tons/ha (lower than the potential of intensively managed land), accompanied by ecological impacts such as peat degradation, deforestation, and land conflicts. In contrast, smart farming has the potential to increase national rice productivity by 10–20%, add up to 3 million tons of unhusked rice (milled dry paddy) if applied to 50% of existing rice fields, save water by 20–50%, and reduce chemical fertilizer use by around 20% through precision application. Conclusion: This study contributes by providing a conceptual and empirical basis that Indonesia’s food security transformation should shift from an expansive model toward inclusive precision intensification, based on agricultural digitalization, strengthening farmer institutions, and utilizing domestic research outputs. It also opens opportunities for further research on designing smart farming implementation models for smallholder farmers and institutional strategies to accelerate its adoption. Novelty/Originality of this article: This study introduces a paradigm shift from land-expansion food estates toward inclusive precision intensification, integrating smart farming, farmer institutions, and digital agriculture as sustainable strategies for Indonesia’s future food security transformation.